Diversity of lactic acid bacteria from Miang, a traditional fermented tea leaf in northern Thailand and their tannin-tolerant ability in tea extract - Siriporn Chaikaew (2018)
© 2017, The Microbiological Society of Korea and Springer-Verlag GmbH Germany. The microbiota of lactic acid bacteria (LAB) in thirty-five samples of Miang, a traditional fermented tea leaf product, collected from twenty-two different regions of eight provinces in upper northern Thailand was revealed through the culture-dependent technique. A total of 311 presumptive LAB strains were isolated and subjected to clustering analysis based on repetitive genomic element-PCR (rep-PCR) fingerprinting profiles. The majority of the strains belonged to the Lactobacillus genera with an overwhelming predominance of the Lb. plantarum group. Further studies of species-specific PCR showed that 201 of 252 isolates in the Lb. plantarum group were Lb. plantarum which were thus considered as the predominant LAB in Miang, while the other 51 isolates belonged to Lb. pentosus. In contrast to Lb. plantarum, there is a lack of information on the tannase gene and the tea tannin-tolerant ability of Lb. pentosus. Of the 51 Lb. pentosus isolates, 33 were found to harbor the genes encoding tannase and shared 93-99% amino acid identity with tannase obtained from Lb. pentosus ATCC 8041T. Among 33 tannase gene-positive isolates, 23 isolates exhibited high tannin- tolerant capabilities when cultivated on de Man Rogosa and Sharpe agar-containing bromocresol purple (0.02 g/L, MRS-BCP) supplemented with 20% (v/v) crude tea extract, which corresponded to 2.5% (w/v) tannins. These Lb. pentosus isolates with high tannin-tolerant capacity are expected to be the high potential strains for functional tannase production involved in Miang fermentation as they will bring about certain benefits and could be used to improve the fermentation of tea products.